2020
DOI: 10.1099/jgv.0.001369
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A/H4N2 mallard infection experiments further indicate zanamivir as less prone to induce environmental resistance development than oseltamivir

Abstract: World HealtH orgaNizatioN geneva orgaNiSatioN moNdiale de la SaNté genève annual subscription / abonnement annuel sw. fr. / Fr. s. 346.-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Following oesophageal inoculation, all mallards were infected starting at 1 day p.i. and followed similar shedding pattern as seen in previous experiments using the same bird model [29–32, 34, 35]. These experimentally infected mallards successfully infected the contact mallards (gen. 2) ( in Methods).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Following oesophageal inoculation, all mallards were infected starting at 1 day p.i. and followed similar shedding pattern as seen in previous experiments using the same bird model [29–32, 34, 35]. These experimentally infected mallards successfully infected the contact mallards (gen. 2) ( in Methods).…”
Section: Resultssupporting
confidence: 79%
“…AIVs replicating in the intestines of wild waterfowl can thus get exposed to OC allowing for resistance development. Several in vivo studies exposing AIV-infected mallards to NAIs in experimental settings mimicking the natural exposure, support the occurrence of resistance development via this route [29–33]. For example, a low pathogenic AIV H1N1 strain developed oseltamivir resistance through the NA-H274Y (N2 numbering) amino acid substitution in the neuraminidase (NA) gene when exposed to 950 ng l –1 OC (the same magnitude as found in river water) in the water source of the mallards [34].…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not find any change at these 2 sites in all H4N2 viruses, indicating that they retained the avian-like receptor-binding preference ( Naeve et al, 1984 ; Matrosovich et al, 2000 ). The absence of E119G and H274N mutations on NA indicated that there were no neuraminidase inhibitors ( NAIs ) resistance mutations ( Tepper et al, 2020 ). No amino acid deletions were observed in the NA stalk region.…”
Section: Resultsmentioning
confidence: 99%
“…fish, daphnids and others (ChV). In compliance with the benchmarking criteria all the intermediates were characterized with a log Kow of ≤ 5 and, a BCF value of < 5000 L/kg, suggesting that these TPs did not exhibit the risk of bioaccumulation and associated biomagnification ( Tepper et al, 2020 ). Also, according to the PBT criteria proposed by US-EPA and the European Commission (EC), none of the produced TPs exhibited long-range transport potential in water bodies ( Table S5 ).…”
Section: Quantitative Analysis With Eps-subtypes and Secondary Structure Proteinsmentioning
confidence: 89%